Naringenin restores neuronal membrane electro-biophysical homeostasis: insights from EIS circuit modeling and molecular dynamics - Yiyao Zhang; Cai You; Shimeng Sun; Tian Fang; Qing Ma; Shangwei Huang; Yi Ding; Han Li; Yiyong Chen; Jianfei Zhang; Jia Xu (Frontiers in Medicine, 2026)
Introduction Naringenin (NGN), a bioactive flavonoid derived from Citri Reticulatae Pericarpium, exhibits considerable neuroprotective properties. However, the precise mechanisms underlying its restoration of neuronal membranes during oxidative stress remain elusive. Methods This study utilized an integrated multiscale approach combining network pharmacology, electrical impedance spectroscopy (EIS) with an eight-element equivalent circuit model, biochemical assays, and molecular dynamics (MD) simulations to systematically evaluate NGN's effects on H2O2-induced injury in HT22 neurons. Results EIS analysis revealed that NGN significantly restored membrane biophysical integrity, reflected by the recovery of critical electro-biophysical parameters (Rm, Cm and fc1) at subcellular resolution. Concurrently, biochemical analyses showed that NGN activates the NRF2/HO-1 signaling pathway, resulting in elevated superoxide dismutase (SOD) activity and decreased malondialdehyde (MDA) levels, thereby enhancing endogenous antioxidant defenses. Furthermore, molecular docking and MD simulations confirmed at the atomic level that NGN forms highly stable, high-affinity complexes with core antioxidant and anti-apoptotic targets, including NRF2, HO-1, and BCL-2. Discussion These findings collectively indicate that NGN exerts a dual neuroprotective mechanism involving both biochemical antioxidant defense and biophysical membrane restoration. Integrating traditional pharmacology with modern biophysical modeling, this study positions EIS as an innovative, label-free approach for monitoring membrane protection, thereby establishing an electrophysiology-based platform for both mechanistic investigation and clinical translation of flavonoids in neuroprotection.